Analisa Tingkat Kematangan Tata Kelola Sistem Teknologi Informasi dan Komunikasi (Studi Kasus : UPT Perpustakaan STMIK Palangkaraya) - Arliyana, Arliyana (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2018)
The use of information and communication technologies continue to grow each year. This is in line with the increasing demands for the distribution of information quickly and accurately. To keep the system of information and communication technologies into one quality enhancer in a College, then required the existence of a system of governance audit of information technology communications so that all factors are interconnected with the use of information technology can run as expected and all service information and communication technology can continue to be improved by the application of information technology is right on target. The existence of a good system of governance is the answer for the use of information and communication technology systems that are reliable. The role of the audit of the governance system of information and communication technologies as a means of decision makers is needed by a college to ensure that the application of information technology is in compliance with the planning. The COBIT frameworks has a coverage of control purposes which consists of 4 domains (ITGI, 2007), that is Planning and Organization (PO), Acquisition and Implementation (AI), Delivery and Support (DS), and Monitor and Evaluate (ME). In addition to this COBIT framework also has a Maturity Model that is used to find out the position of the maturity of the current governance and continuously strive to improve the level up to the highest level in order for all aspects of the management towards information technology can be done more effectively. Then the results of this research is the description of the analysis of the level of maturity of the implementation of the corporate governance of information and communication technology systems using COBIT framework 4.1 on Library STMIK Palangkaraya.